CORRELATION BETWEEN SCIENCE ANXIETY AND CHOICE OF SUBJECT AMONG JUNIOR SECONDARY SCHOOL STUDENTS IN ENUGU STATE, NIGERIA - Eze, Forster (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Previous research has underscored the critical role of science anxiety in the declining science education in developing countries. However, little is known about the relationship between science anxiousness and students' subject preference. The present paper examined the correlation between science anxiety and choice of subject among junior secondary school students. One hundred and sixty-six students drawn from public and private secondary schools in the Enugu State participated in the study. They completed a self-report measure of science anxiety with demographic information. Pearson's product-moment correlation was performed to determine the correlation between science anxiety and students' choice of subject. The result revealed a statistically significant, moderate positive correlation between science anxiety and students' choice of subject, r (164) = .42, p < .001. Most importantly, observation of the R2 revealed that science anxiety explained about 21% of the variation in the choice of subject. Thus, the study concludes that science anxiety is positively associated with students' choice of subject in the secondary school classroom.